Investigation of probability distribution laws of structural properties of nanoparticles simulated by molecular dynamics method - Vakhrushev, Alexander Vasil'evich; Fedotov, Alexey Yur'evich (Computational Continuum Mechanics, 2009)
A mathematical model of condensation of composite nanoparticles in a gas phase is presented. A series of computational experiments are carried out to simulate the formation of nanoparticles. Statistical data on the dimensional, structural and quantitative properties of metal nanoparticles are obtained. The estimating characteristics of sampled data are calculated. Statistical hypotheses concerning the probability distribution laws of the properties of nanoparticles are verified using the Pearson criterion. Histograms showing the distribution of the number of nanoparticles per unit volume, their average diameter and density, and the fraction of total mass of silver in nanoparticles are constructed.
Keywords: nanoparticles; nanocomposites; molecular dynamic; probability; distribution; properties of nanoparticles